Corporate finance : a focus approach - Ehrhardt, Michael C., 1955- (South-Western, Cengage Learning, 2011)
Focus on the financial concepts, skills, and technological applications that are most critical for MBA students in today's workplace with Ehrhardt/Brigham's CORPORATE FINANCE: A FOCUSED APPROACH, 4E. This lean text provides an in-depth treatment of all topics essential to corporate finance within a streamlined presentation that you can complete in a single semester. Your students review the latest financial developments -- from the collapse of the sub-prime mortgage market to the financial and global economic crisis -- as this edition shows them how to maximize a firm's value in today's changed world. Numerous recent examples illustrate the relevance of what students are learning, while Excel Tool Kits, "Build a Model" problems, and Mini-Case Spreadsheets help students master the many functions of Excel. Students even gain hands-on experience with the same tool Wall Street professionals use daily with new Thomson ONE-Business School Edition problems. Trust this book's concise, focused presentation to clearly demonstrate how and why corporations make specific financial decisions.